The Underlying Mechanism of Paeonia lactiflora Pall. in Parkinson’s Disease Based on a Network Pharmacology Approach - Du, Wanqing; Liang, Xiao; Wang, Shanze; Lee, Philip; Zhang, Yunling (Frontiers in Pharmacology, 2020)
Background Parkinson's disease (PD) is the second most common neurodegenerative disease worldwide, yet as of currently, there is no disease-modifying therapy that could delay itsprogression. Paeonia lactiflora Pall. is the most frequently used herb in formulas for PD in Traditional Chinese Medicine, and also a potential neuroprotective agent for neurodegenerative diseases, while its mechanisms remain poorly understood. In this study, we aim to explore the underlying mechanism of Paeonia lactiflora P. in treating PD utilizing a network pharmacology approach. Methods The protein targets of Paeonia lactiflora P. ingredients and PD were first obtained from several databases. To clarify the key targets, a Protein-Protein-Interaction (PPI) network was constructed and analyzed on the String database, and then enrichment analysis was performed by the Metascape platform to determine the main GO biological processes and KEGG pathways. Finally, the Ingredient-Target-Pathway (I-T-P) network was constructed and analyzed by Cytoscape software. Results 6 active ingredients of Paeonia lactiflora P. (kaempferol, β-sitosterol, betulinic acid, palbinone, paeoniflorin and (+)-catechin), as well as 6 core targets strongly related to PD treatment (AKT1, IL6, CAT, TNF, CASP3 and PTGS2) were identified. The main pathways were shown to involve neuroactive ligand-receptor interaction, Calcium signaling pathway, PI3-Akt signaling pathway, TNF signaling pathway, apoptosis signaling pathway. The main biological process included the regulation of neurotransmitter levels. Conclusions Paeonia lactiflora P. may retard neurodegeneration by reducing neuroinflammation, inhibiting intrinsic and extrinsic apoptosis, and may improve motor and non-motor symptoms by regulating the levels of neurotransmitters. Our study has revealed the multi-component, multi-target and multi-pathway mechanism of Paeonia lactiflora P. in the treatment of PD, and may contribute to novel drug development for PD.